Oil and Governance State-Owned Enterprises and the World Energy Supply - Victor, David G.; Hults, David R.; Thurber, Mark C. (Cambridge Cambridge University Press, 2012)
"National Oil Companies (NOCs) play an important role in the world economy. They produce most of the world's oil and bankroll governments across the globe. Although NOCs superficially resemble private-sector companies, they often behave in very different ways. Oil and Governance explains the variation in performance and strategy for NOCs and provides fresh insights into the future of the oil industry as well as the politics of the oil-rich countries where NOCs dominate. It comprises fifteen case studies, each following a common research design, of NOCs based in the Middle East, Africa, Asia, Latin America and Europe. The book also includes cross-cutting pieces on the industrial structure of the oil industry and the politics and administration of NOCs. This book is the largest and most systematic analysis of NOCs to date and is suitable for audiences from industry and academia, as well as policy makers"--Provided by publisher.
Handcuffed : an assessment of Pemex's performance and strategy Brazil's Petrobras : strategy and performance The political economy of expropriation and privatization in the oil sector Awakening giant : strategy and performance of the Abu Dhabi National Oil Company NNPC and Nigeria's oil patronage ecosystem Petróleos de Venezuela, S.A. (PDVSA) : from independence to subservience Fading star : explaining the evolution of India's ONGC China National Petroleum Corporation (CNPC) : a balancing act between enterprise and government Sonatrach : the political economy of an Algerian state institution Kuwait Petroleum Corporation (KPC) : an enterprise in gridlock Petronas : reconciling tensions between company and state Oil, monarchy, revolution, and theocracy : a study on the National Iranian Oil Company (NIOC) Angola's Sonangol : dexterous right hand of the state Saudi Aramco : the jewel in the crown Norway's evolving champion : Statoil and the politics of state enterprise On the state's choice of oil company : risk, management, and the frontier of the petroleum industry Major conclusions and implications for the future of the oil industry Hybrid governance : state management of national oil companies Gazprom : the struggle for power Varun Rai -- Nadejda Victor and Inna Sayfer -- Mark C.Thurber, Ifeyinwa M. Emelife and Patrick R. P. Heller -- Varun Rai and David G. Victor -- Leslie Lopez -- Patrick R.P. Heller -- David G. Victor, David R. Hults, and Mark C. Thurber. Mark C. Thurber and Benedicte Tangen Istad -- John P. Entelis -- Adilson de Oliveira -- David R. Hults -- Binbin Jiang -- Paul Stevens -- Ognen Stojanovski -- Paasha Mahdavi -- Paul Stevens -- Peter A. Nolan and Mark C. Thurber -- David R. Hults -- Christofer Warshaw --
Includes bibliographical references (pages 946-999) nd index.
Electronic reproduction.
Keywords: Petroleum industry and trade -- History; Petroleum industry and trade -- Government policy; Corporations, Government; Electronic book